DEIXIS IN NIKI ZEFANYA’S SONG LYRICS LIVE AT WILTERN ALBUM - Hidayatul Luthfiya Azizah; Adip Arifin (IKIP Siliwangi, 2024)
The present study attempts to investigate the types of deixis in Niki Zefanya’s song lyrics Live at Wiltern album. Furthermore, it also investigates the most dominant deixis type realized in Niki Zefanya’s song lyrics Live at Wiltern album. To analyze the findings, Levinson’s theory (1983) on deixis is used. The study employs descriptive qualitative method. The data are taken from five songs within Live at Wiltern album (2023). The findings of research reveals a total of 522 data on the whole deixis type. Starting form the most dominant one, person deixis was found in a total of 312 findings or equal to 60% of the whole findings, followed by temporal deixis, 115 findings (22%), spatial deixis 56 findings (11%), social deixis 31 findings (6%), and discourse deixis 8 findings (1%). Based on the result of the study, it is highly suggested for other researcher to consider expanding the analysis to a broader range of musical genres and artists.